The effects of hydrological connectivity blocking on Suaeda salsa development in the Yellow River Delta, China - Wang, XueHong; Zou, YuHan; Zhu, Tao; Guan, Bo; Yang, JiSong; Yu, JunBao (Frontiers in Ecology and Evolution, 2022)
Blocking of hydrological connectivity could greatly impact the sediment deposition process and change water and salinity conditions, which in turn affect plant germination, growth, and development in delta wetlands. A two-year experiment, which included the effects of soil burial, water, and salinity on germination, growth, and production, was conducted to examine the function of hydrological connectivity blocking on the development of Suaeda salsa, a halophyte species. The results demonstrated that soil burial, water, and salinity all had significant effects on seed germination, plant growth, and production (p < 0.05). Seed germination decreased as soil buried depth increased (< 4 cm), and seeds did not germinate successfully when the buried depth was > 4 cm. Seed germination was the highest at 0 cm burial. However, moderate burial was beneficial for seedling emergence; therefore, the survival rate was the lowest when seeds were distributed at the surface (0 cm). Water and salinity both significantly affected the germination, growth, and productivity of S. salsa. Moderate salinity (10 - 20 g/kg) and fluctuating water (0–10 cm water depth) were suitable for seed germination and plant growth. Low salinity (< 10 g/kg), High salinity (>20 g/kg), drought, and high water levels (long-term flooding with water depth >10 cm) were not conducive to the growth of S. salsa, and biomass and seed yield were also reduced. As a halophyte, salinity that is too low or too high is unsuitable for S. salsa population. Water and salinity also significantly affected S. salsa population (p < 0.05). In particular, water can offset the hazards of high salt concentrations. Blocking of hydrological connectivity can influence seed germination, yield, and vitality. In this case, S. salsa may have died out from the coastal wetland due to the lack of hydrological connectivity restoration.